2012
DOI: 10.1074/mcp.m112.017640
|View full text |Cite
|
Sign up to set email alerts
|

Serum Proteomic Signature of Human Chagasic Patients for the Identification of Novel Potential Protein Biomarkers of Disease

Abstract: Chagas disease is initiated upon infection by Trypanosoma cruzi. Among the health consequences is a decline in heart function, and the pathophysiological mechanisms underlying this manifestation are not well understood. To explore the possible mechanisms, we employed IgY LC10 affinity chromatography in conjunction with ProteomeLab PF2D and two-dimensional gel electrophoresis to resolve the proteome signature of high and low abundance serum proteins in chagasic patients. MALDI-TOF MS/MS analysis yielded 80 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 76 publications
0
41
1
Order By: Relevance
“…This suggested that carbonylated DBP is found in human serum as recently described for rat serum [55]. To investigate whether carbonylated DBP is found in human serum we immunoprecipitated DBP from freshly drawn human blood and either derivatized it with 2,4-dinitrophenyl hydrazine to detect carbonylated DBP or left it untreated before Western blot analysis with anti-DNP antibodies.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…This suggested that carbonylated DBP is found in human serum as recently described for rat serum [55]. To investigate whether carbonylated DBP is found in human serum we immunoprecipitated DBP from freshly drawn human blood and either derivatized it with 2,4-dinitrophenyl hydrazine to detect carbonylated DBP or left it untreated before Western blot analysis with anti-DNP antibodies.…”
Section: Resultsmentioning
confidence: 73%
“…Carbonylation is a protein modification induced by oxidative stress [54], and increased carbonylation of serum proteins including DBP is seen during inflammatory responses [55-57]. Carbonylation of DBP could lead to a higher concentration of free 25(OH)D 3 due to a reduced affinity of carbonylated DBP for 25(OH)D3 and/or increased degradation of DBP.…”
Section: Resultsmentioning
confidence: 99%
“…ETS1, GATA2 and AR modulate the activity of vinculin (VCL), which has been previously associated with dilated cardiomyopathy [57,58]. Furthermore, we found that GATA2 is a regulator of NPPB, which encodes BNP, a well-established clinical biomarker for decompensated heart failure [59].…”
Section: Accepted Manuscriptmentioning
confidence: 83%
“…Research by Wen et al [51] focused on improving the ability to diagnose Chagas disease identified a proteomic signature for patients with CCC to allow for earlier detection of disease. Another study focused on the development of therapeutic approaches using stem cells as alternatives to transplantation.…”
Section: Nhlbi–funded Research On Chagas Diseasementioning
confidence: 99%